The refuge [large type] - Gabhart, Ann H., 1947- (Center Point Large Print, 2019)
"Darcie and Walter Goodwin join a Shaker village to escape a cholera epidemic, but when Walter dies, Darcie is left alone--and lonely. Can love live again for this widow in a community that doesn't believe in marriage?"--